2006
DOI: 10.1021/jp0609378
|View full text |Cite
|
Sign up to set email alerts
|

Why tert-Butyl Alcohol Associates in Aqueous Solution but Trimethylamine-N-oxide Does Not

Abstract: In dilute aqueous solution, tert-butyl alcohol (TBA) tends to aggregate but trimethylamine-N-oxide (TMAO) does not. Given that both molecules have very similar geometry with hydrophobic and hydrophilic groups, it is interesting to ask why they behave so differently in aqueous solution. To explore this question, we use molecular dynamics simulations to study two models representing TBA and TMAO that differ essentially only in their electrostatic properties. It is shown that this difference is sufficient to give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
109
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(127 citation statements)
references
References 39 publications
18
109
0
Order By: Relevance
“…The strong hydration of TMAO has been previously demonstrated in both experiments and simulations. [30][31][32][33][34][35] Urea is a nearly ideal solute in aqueous solution (in the molar scale); is smaller and correspondingly shows more modest correlations with water.…”
Section: Resultsmentioning
confidence: 99%
“…The strong hydration of TMAO has been previously demonstrated in both experiments and simulations. [30][31][32][33][34][35] Urea is a nearly ideal solute in aqueous solution (in the molar scale); is smaller and correspondingly shows more modest correlations with water.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of clustering for TMAO agrees with the results of molecular dynamics simulations. 39 For TBA, the saturation effect is much stronger, indicating that these molecules cluster. For TBA, only the low concentration region can be fitted well to Eq.…”
Section: Discussionmentioning
confidence: 99%
“…16,4,20,39,40 MD simulations showed that for a mole fraction of 0.08, clusters of 3-4 TBA molecules were formed. 40 Neutron scattering studies for a TBA solution of 0.06 mol fraction also showed that clusters are formed with a size of 3 Ϯ 0.5 TBA molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several simulation studies [42][43][44][45][46][47][48][49][50] have been performed on this important binary mixture, at different concentrations and using different force fields. Early in the 1990's, Tanaka and Nakanishi [42] performed simulations on this system and noted self-aggregation of TBA molecules at mole fraction 0.17.…”
Section: Introductionmentioning
confidence: 99%